2017
DOI: 10.1371/journal.pone.0169649
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale Population Assessment of Physical Activity Using Wrist Worn Accelerometers: The UK Biobank Study

Abstract: BackgroundPhysical activity has not been objectively measured in prospective cohorts with sufficiently large numbers to reliably detect associations with multiple health outcomes. Technological advances now make this possible. We describe the methods used to collect and analyse accelerometer measured physical activity in over 100,000 participants of the UK Biobank study, and report variation by age, sex, day, time of day, and season.MethodsParticipants were approached by email to wear a wrist-worn acceleromete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
946
7
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 838 publications
(988 citation statements)
references
References 20 publications
32
946
7
3
Order By: Relevance
“…As greater compliance rates will provide the researcher with activity data over more days and capture a greater proportion of that day, researchers will have more confidence that the data collected is representative of habitual PA. As will recent findings which showed that wristworn accelerometers is highly acceptable to participants with a median wear-time of 6Á9 days and the very high proportion of people (103 578 of 106 053 (98%)) in whom the data were of high quality and completeness (Doherty et al, 2017). These findings will provide confidence to researchers given the well-established relationships between physical activity and successful ageing (Dogra & Stathokostas, 2012;Almeida et al, 2014) and adiposity markers (Jensen et al, 2014).…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…As greater compliance rates will provide the researcher with activity data over more days and capture a greater proportion of that day, researchers will have more confidence that the data collected is representative of habitual PA. As will recent findings which showed that wristworn accelerometers is highly acceptable to participants with a median wear-time of 6Á9 days and the very high proportion of people (103 578 of 106 053 (98%)) in whom the data were of high quality and completeness (Doherty et al, 2017). These findings will provide confidence to researchers given the well-established relationships between physical activity and successful ageing (Dogra & Stathokostas, 2012;Almeida et al, 2014) and adiposity markers (Jensen et al, 2014).…”
Section: Introductionmentioning
confidence: 75%
“…Of the several different types of accelerometers available (Actical, Actiwatch, GENEActiv, Axivity, etc. Despite recent findings which question the classification accuracy of wrist accelerometry processing methods (Ellingson et al, 2017), the use of wrist-worn accelerometers to characterize activity patterns in large cohorts of individuals is now common (Doherty et al, 2017;Menai et al, 2017;NHANES, 2018). Historically accelerometers were worn on the waist to reflect whole body movement and thus energy expenditure but poor compliance and subsequent selection bias and misclassification (Troiano et al, 2014) has seen increased use of wrist-worn accelerometers to assess habitual PA. Wrist-worn accelerometers have also been validated against established measures of physical activity energy expenditure (van Hees et al, 2011;Hildebrand et al, 2014;White et al, 2016) and have shown to provide high (85%-97%) activity classification accuracies when using machine learning models (Zhang et al, 2012;Mannini et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Raw accelerometer data were processed using GGIR V1.5-9 package (R Core Team, Vienna, Austria) (https://cran.rroject.org/web/packages/GGIR/index.html) [3]. We defined MVPA using a 100 milligravity (m g ) cut-off, based on laboratory findings [4].…”
Section: Methodsmentioning
confidence: 99%
“…The physiological activity tracking data generated at home can also be used to improve the existing therapies and study recovery variations over a wider population. Motion sensors combined with temperature and pulse sensors will see a wider acceptance in public and clinical practice [2,10].…”
Section: Introductionmentioning
confidence: 99%